A Mathematical Model For The Dynamics of Polio. - Owobusingye, Johnan (Kabale University, 2024)
There is a lack of treatment for poliomyelitis and it is only prevented through immunization with live oral polio vaccine (OPV) or/and inactivated polio vaccine (IPV). Poliomyelitis is a very contagious viral infection caused by poliovirus. Children are principally attacked. In this project, we assessed the impact of vaccination in the control of the spread of poliomyelitis via a deterministic SVElR (Susceptible-Vaccinated-Exposed-Infectious-Recovered) model of infectious disease transmission, where vaccinated individuals are also susceptible, although to a lesser degree. Using Lyapunov-Lasalle methods, we proved the global asymptotic stability of the dynamics of the disease whenever Ra < I. Numerical simulations, using poliomyelitis data from Kabale Regional Referral Hospital in Kabale district, have been conducted to approve analytic results and to show the importance of vaccination coverage in the control of disease spread.